Sosialisasi Interaktif: Karakter dan Kebutuhan Gen Z Berdasarkan Perspektif Guru BK - Moesarofah Moesarofah; Aniek Wirastania; Cindy Asli Pravesti; Sutijono Sutijono; Alyssa Rosalia Dewi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service activity aims to improve the understanding of Guidance and Counseling Teachers regarding the character and needs of Generation Z in school services. Gen Z as a digital generation has a communicative, visual, adaptive character to technology, but is vulnerable to psychosocial stress. The activity was carried out through interactive socialization to 80 high school/vocational high school guidance and counseling teachers who are members of the Surabaya area MGBK. The activity method included material delivery, case discussions, questions and answers, practical reflection, and evaluation through a post-test questionnaire. The questionnaire results showed an overall average of 3.65 in the high category. The aspects of understanding Gen Z's character, the need for guidance and counseling services, and readiness for adaptive guidance and counseling implementation were in the high category, while case analysis skills were in the sufficient category. These findings indicate that interactive socialization is relevant to strengthening the understanding of guidance and counseling teachers, but further training based on case studies and counseling practices is still needed so that guidance and counseling services are more adaptive to the needs of Gen Z students. This activity also emphasized the importance of a dialogic, contextual, and needs-based approach to students.